Comparison of thyroid hormonal status and serum albumin level between children with moderate acute malnutrition and severe acute malnutrition - Saini, Aashish; Jain, Hemant; Doshi, Mili; Saini, Jinesh (International Journal of Contemporary Pediatrics, 2022)
Background: Malnutrition is one of the most common nutritional problems in developing countries of the world and an important cause of childhood mortality and morbidity leading to permanent impairment of physical and mental growth. Objective of current study was comparison of thyroid hormonal status and serum albumin level between children with MAM and SAM. Methods: The present study was a hospital-based Descriptive comparative study. A total of 96 children aged 6 months to 5 years were enrolled. They were divided into two groups (MAM and SAM) based on WHO staging for malnutrition. A detailed clinical examination was done. Thyroid function test and Serum albumin were done. Statistical analysis was performed. Results: Children with SAM have low levels of albumin, T3, T4, FT4 as compared to children with MAM. The difference was statistically significant (p value <0.01). The Serum TSH levels were comparable among two groups. Significant positive correlation between mean T3 and T4 levels of children with MAM with serum albumin was observed and significant positive correlation of T3, T4, and FT4 was observed in SAM. Serum TSH level in both categories does not correlate with serum albumin. Conclusions: Children with MAM and SAM have low albumin levels probably due to decreased intake of proteins and reduced biosynthesis. Serum T3, T4 and FT4 levels are lower in children with MAM and SAM probably due to reduction in circulating plasma proteins.